Changing Patterns of violence in the Western Sahel - Krienke, Hannah (University of the Witwatersrand, Johannesburg, 2024)
This dissertation investigates how changing patterns of violence in Mali and Burkina Faso have resulted in the formation of alternative government systems by jihadist groups and community militias. By analysing the interactions between these non -state actors, state institutions, and foreign intermediaries, the study highlights the significant impacts of socioeconomic problems, corruption, ethnic and religious tensions, and climate change, which have given rise to space where power and control of the state is contested. In Mali, violence erupted in 2012 with an insurgent movement that was exacerbated by subsequent coups and political crises, eroding state authority and supporting the growth of multiple armed groups most notably via jihadist insurgency. Violence in Burkina Faso began to grow in 2015, and it was exacerbated with the 2022 coup, which altered the dynamics of domestic and foreign alliances, including the Russian Wagner Group's involvement. Both countries are currently governed by the military, although in both cases the military has struggled to calm violence. The frequency of attacks increasing drastically between 2015 and 2024. Therefore, the dynamics of violence in both countries are examined in relation to the restructuring of local and state interactions and the emergence of new forms of governance. This involves drawing on theories such as Mary Kaldor's t "new wars," who emphasises the relationship between identity politics and armed conflict. Through a comparative examination, the study reveals parallels as well as differences in the ways that violence has impacted state formation and impacted Sahelian populations in Mali and Burkina Faso.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Sahel; Mali; Burkina Faso; Violence; Patterns; SDG-16: Peace, justice and strong institutions